Junk Food Advertisements in Cartoon Channel MBC3 Influence on Children in Jordan - Alhuneiti, Kholod Saleh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Childhood obesity has become a serious global issue, and there is a need to check the size and magnitude of the level that it has reached. This study, seeks to explore whether junk food advertisements broadcast on the children‘s cartoon channel MBC3, have had an attributable influence on increases in child obesity, and to what extent children‘s behaviour is influencing the consumption of junk food. This study seeks to highlight different reasons that lead to an increase in obesity among Jordanian children. The study took place in Jordan and employed qualitative methodology. Content analysis is used to collect data from television advertisements. The data gathering was achieved by conducting semi-structured interviews with children; with a further collective focus group interview. Finally, the researcher used her own field notes during the research. In conclusion, to what extent the influence from junk food advertisements in cartoon channels affects child food eating behavior, matched with and the corresponding relationship in the increases in childhood obesity among Jordanian children. Results indicate the significant influence that is derived from cartoon channel junk food advertisements. The outcomes of the study shed light to the fact that media play a significant rule in the increase of childhood obesity.

ÖZ: Çocuk obezitesi tüm dünyada önemli bir konu haline gelmiştir ve bunun boyutunu ve ulaştığı seviyeyi kontrol etmeye gereksinim vardır. Bu çalışma, aburcubur türü gıdaların, çocuk çizgi film kanalı MBC3‘deki reklamların, çocuk obezitesine etkisi olup olmadığını ve aburcubur gıda tüketiminde ne ölçüde etkili olduğunu araştırmayı amaçlamaktadır. Bu çalışma Ürdündeki çocuk obezitesinin artmasına yol açan farklı nedenlere ışık tutmayı hedeflemektedir. Çalışma Ürdün‘de yer almıştır ve nitel yöntem kullanılmıştır. Televizyon reklamlarından veri toplamada içerik analizi kullanılmıştır. Veri toplama çocuklarda yapılan yarı-yapılı mülakatlar, ve odak grup mülakatlarıyla yapılmış, son olarak araştırmacı çalışma süresince kendi tuttuğu alan notlarını kullanmıştır. Sonuç olarak, Ürdünlü çocukların çizgi film kanallarındaki aburcubur gıda reklamlarından ne ölçüde çocukların yeme alışkanlıklarını etkilediği, çocuk obezitesi artışıyla ilişkili bulunmuştur. Sonuçlar çizgi film kanallarındaki aburcubur gıda reklamlarının önemli sonuçları olduğunu göstermektedir. Bu çalışmanın sonuçlarının Ortadoğudaki Arab ülkelerindeki medyanın çocuk obezitesinin artmasında önemli etken olduğu gerçeğini aydınlatmaktadır.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2017. Supervisor: Assoc. Prof. Dr. Bahire Efe Özad.
Keywords: Communication and Media Studies; TV Advertising--Jordan; Television advertisements; cartoon channels; childhood-obesity; junk food